Listo, as a conversational colloquial spanish particle in Medellín (Colombia) - Ortiz Correa, Adriana María (2021)
This article analyzes LISTO, as a colloquial conversational particle used by speakers in Medellín, Colombia. Firstly, it studies how the grammaticalization of this adjective has been changing it. Then, it focuses on this unit position in order to describe how it shows in different contexts and the different discursive pragmatic functions of it in dialogues and monologues as a way to contribute to the communication exchange. This study is based on fourteen spontaneous conversations recordings, PRESEEA´s oral interviews recorded in Medellín and as a complement, other examples taken from oral and written texts. The conclusions stand out from corpora three discursive functions of LISTO: deontic which reflects the agreement between speakers, supplement validation or checking and metadiscursive conversational or discourse arrange.